Phylogeny and Morphological Variability of Trypanosomes from African Pelomedusid Turtles with Redescription of Trypanosoma mocambicum Pienaar, 1962 - Dvořáková, Nela; Čepička, Ivan; Qablan, Moneeb A; Gibson, Wendy; Blažek, Radim; Široký, Pavel (Protist, 2015)
Little is known about host specificity, genetic diversity and phylogenetic relationships of African turtle trypanosomes. Using PCR targeting the SSU rRNA gene, we detected trypanosomes in 24 of 134 (17.9%) wild caught African pelomedusid turtles: Pelusios upembae (n=14), P. bechuanicus (n=1), P. rhodesianus (n=3) and P. subniger (n=6). Mixed infection of Trypanosoma species was confirmed by PCR in three specimens of P. upembae, and in one specimen each of P. bechuanicus, P. rhodesianus, and P. subniger. Microscopic examination of stained blood smears revealed two distinct forms (broad and slender) of trypomastigotes. The broad form coincided in morphology with T. mocambicumPienaar, 1962. Accordingly, we have designated this form as the neotype of T. mocambicum. In phylogenetic analysis of the SSU rRNA gene, all the new turtle trypanosome sequences grouped in a single clade within the strongly supported "aquatic" clade of Trypanosoma species. The turtle trypanosome clade was further subdivided into two subclades, which did not correlate with host turtle species or trypanosome morphology. This study provides the first sequence data of Trypanosoma species isolated from freshwater turtles from tropical Africa and extends knowledge on diversity of trypanosomes in the Afrotropical zoogeographical realm.
Keywords: fylogeneze; Sequence Analysis, DNA; Phylogeny; sekvenční analýza DNA; molekulární sekvence - údaje; Afrika; Turtles; RNA, Protozoan; SSU rRNA gene.; Pelusios; Animals; Africa; turtle; zvířata; RNA protozoální; Molecular Sequence Data; phylogeny; želvy; Trypanosoma; polymorphism